Predicting depression, anxiety and self-harm in adolescents: the role of perfectionism and acute life stress. - O'Connor, R; Rasmussen, S; Hawton, K (2010)
Despite the growing evidence that perfectionism is associated with adolescent psychological distress, few studies have investigated this relationship prospectively with measures designed for use in adolescent populations. In the present study, within a diathesis-stress framework, we investigated the extent to which perfectionism and acute life stress predict depression, anxiety and self-harm among adolescent school children (n = 515) over a 6 month period (Time 1-Time 2). Socially prescribed perfectionism (SPP), self-oriented perfectionism-critical (SOP-critical) and the associated interactions with acute life stress differentially predicted anxiety, depression and self-harm. Acute life stress was an independent predictor of depression, anxiety and self-harm. SPP predicted depression and interacted with acute life stress to predict self-harm. SOP-critical and the SOP-critical by acute life stress interaction predicted anxiety. Self-oriented perfectionism-striving (SOP-striving) did not predict any of the Time 2 measures of distress. The dimensions of perfectionism are differentially associated with psychological distress. Tailored clinical interventions focused on adolescent perfectionism should offer promise in tackling psychological morbidity in adolescence.